2021
DOI: 10.1002/smll.202104554
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Confined Reaction Based on Host–Guest Interaction Using Single‐Molecule Conductance Measurement

Abstract: the reaction dynamics of confined reaction in millimolar concentration scale efficiently. However, NMR, isothermal titration calorimetry, and thermogravimetry are challenging to obtain the dynamic changes during confined reaction at micromolar concentrations (5 × 10 −6 m) relative to conventional reactions, which is due to its complex multimolecular interactions, [10] and the poor solubility results in concentrations in the solution below the detection range of conventional methods. [11] The test methods that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Recently, Hong's group reported a novel method to characterize the dimerization process of the guest 1,2-bis(4-pyridinyl) ethylene (BPE) in CB [8] using the STMBJ. 89 By mixing BPE and CB [8], two BPE molecules are encapsulated into the cavity of CB [8], leading to the formation of a BPE dimer (BPE 2 ) upon laser irradiation. Electrical conductance of the BPE monomer, a mixture of 2BPE@CB [8] and BPE, dimerization compound BPE 2 @CB [8] is measured using RT by anchoring the pyridine group.…”
Section: Rt Platform Applicationsmentioning
confidence: 99%
“…Recently, Hong's group reported a novel method to characterize the dimerization process of the guest 1,2-bis(4-pyridinyl) ethylene (BPE) in CB [8] using the STMBJ. 89 By mixing BPE and CB [8], two BPE molecules are encapsulated into the cavity of CB [8], leading to the formation of a BPE dimer (BPE 2 ) upon laser irradiation. Electrical conductance of the BPE monomer, a mixture of 2BPE@CB [8] and BPE, dimerization compound BPE 2 @CB [8] is measured using RT by anchoring the pyridine group.…”
Section: Rt Platform Applicationsmentioning
confidence: 99%
“… (a) Schematic illustration of the host‐guest system assisted reaction [79] . 2D conductance histograms of the molecule BPE (b), 2BPE@CB[8] complex (c) and the producted BPE 2 @CB[8] (d).…”
Section: Supramolecular Junctions With Non‐covalent Interactionsmentioning
confidence: 99%
“…Reproduced from Ref. [79] with permission. Copyright 2022, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: σ-σ Stacking Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…[127][128][129][130] By this means, Yuan et al showed that single-molecule junctions formed in an STM-BJ setup could provide a testbed to detect temporal signals from reactants in ultra-low concentrations, which are invisible to methods such as mass spectroscopy. 131 They used hostguest assembly to study the conductance change during complexation of 1,2-bis(4-pyridinyl)ethylene (BPE) monomer and CB [8], and finally the dimerization product to BPE2@CB [8] upon UV irradiation. As seen in Fig.…”
Section: Host-guest Interactionmentioning
confidence: 99%